The influence of food vlogger attributes on content sharing intention and attitudes toward products with emotional bond moderation - Juventus Bangkit Wibowo; Eka Setiawati (Privietlab, 2026)
In recent years, the profession of food vlogging has gained increasing popularity and has become an influential source of information for audiences seeking recommendations on culinary products. Food vloggers play an important role in introducing various types of food and beverages, as well as providing insights into local culinary specialties through digital platforms. Their content not only serves as entertainment but also functions as a reference for consumers in forming perceptions and evaluations of food products. This study aims to examine the influence of food vlogger attributes—namely, attractiveness, trustworthiness, and expertise—on content-sharing intention and attitude toward products, with emotional bonding positioned as a moderating variable. Furthermore, this research investigates the impact of content-sharing intention and product attitude on purchase intention. Data were collected from 320 respondents in Yogyakarta using an online questionnaire distributed via Google Forms with a purposive sampling technique. The collected data were analyzed using the SPSS software. The results indicate that food vlogger attributes have a significant positive effect on content-sharing intention and attitude toward products. Emotional bonding strengthens the relationship between food vlogger attributes and attitudes toward products. Additionally, content-sharing intention positively influences attitudes toward products, which in turn significantly affects purchase intention. These findings suggest that food vloggers with strong personal attributes and emotional connections with their audience can effectively shape consumer attitudes and encourage purchasing decisions.